Argumentation for the Existence of God in the Thought of Yusuf al-Qaradawi - Fauzi Fauzi; Sofiandi Sofiandi; Kailani Kailani (Kutubkhanah, 2025)
The concept of divinity is a fundamental aspect of all human belief systems. For Yusuf al-Qaradawi, the existence of God is the first and highest truth, undeniable by reason or human nature. This study aims to analyze al-Qaradawi's arguments regarding the existence of God and examine their relevance within contemporary theological thought. Employing a qualitative approach with a figure study method (library research), the primary data source is Yusuf al-Qaradawi's work Wujudullah: Eksensian Allah (Risalah Gusti, 2005). The study identifies five main arguments for the existence of God: (1) the argument from nature, (2) the cosmological argument, (3) the argument from precise and accurate measurements, (4) the argument from guidance and direction, and (5) the argument from the history of salvation. All these arguments emphasize that the existence of God is real and inherent in human consciousness, whether directly or indirectly realized. These findings demonstrate that al-Qaradawi successfully integrates theological, philosophical, and empirical approaches to explain the existence of God amid the challenges of modern thought.